A new species of Andean poison frog, Andinobates (Anura: Dendrobatidae), from the northwestern Andes of Colombia - Amézquita, Adolfo; Márquez, Roberto; Medina, Ricardo; Mejía-Vargas, Daniel; Kahn, Ted R.; Suárez, Gustavo; Mazariegos, Luis (Zootaxa, 2013)
The poison frogs of the Colombian Andes, Pacific lowlands and Panamahave been recently recognized as a new, monophyletic and well-supported genus: Andinobates. The species richness and distribution within Andinobates remain poorly understood due to the paucity of geographic, genetic and phenotypic data. Here we use a combination of molecular, bioacoustic and morphometric evidence to describe a new species of Andean poison frog: Andinobates cassidyhornae sp. nov. from the high elevation cloud forests of the Colombian Cordillera Occidental, in the northwestern Andes. The new species is associated to the bombetes group and characterized by a unique combination of ventral and dorsal color patterns. Data on 1119 bp from two mitochondrial markers allowed us to reject the null hypotheses that A. cassidyhornae sp. nov. is part of the phenotypically similar and geographically less distant species: A. opisthomelas, A. virolinensis or A. bombetes. The best available phylogenetic trees and the genetic distance to other Andinobates species further support this decision. Altogether, the advertisement call parameters unambiguously separated A. cassidyhornae sp. nov. calls from the calls of the three closest species. The new species adds to a poorly known and highly endangered genus of poison frogs that requires further studies and urgent conservation measures.